EXACT SOLUTIONS TO A FAMILY OF FITZHUGH-HAGUMO TYPE EQUATIONS - Constantinescu, Dana; Tigan, Gheorghe (Matematichki Bilten, 2007)
A family of partial differential equations of type Fitzhugh-Nagumo is studied in this paper, generalizing a result presented in [7]. After an introduction to the problem, we find the exact solutions of the equation under study. The first integral method is employed.